THE ROLE OF THE ORPHAN CHILD IN CHARLES DICKENS’ OLIVER TWIST - Assist. Lect. Riyadh Mohsen Huwail; Hani Mohammed Saeed Mohammed Ali (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
When Charles Dickens wrote Oliver Twist in the 1830s, crime was a major problem in London. To shed light on this problem, Charles Dickens cared about the reader and used different literary methods to be more influential and more effective in conveying his literary message towards his society. He used literary symbolism to evoke a group of additional meanings that are essential in conveying the desired meaning. His primary aim was to draw the reader's attention to the perception of meaning of what he wanted to convey about the innocent or evil individuals in his novel Oliver Twist, and the symbolism had wide ability to motivate the reader to derive deeper meanings, which enriched the novel by providing hints about the development of the novel's events. Given the importance of these narrative methods, this study decided to conduct a literary analysis to determine the extent of the effect of the role played by literary symbolism in conveying meaning in the novel Oliver Twist